Brand equity and customer repurchase intention towards Agromas products / Ahmad Syakir Kadimin and Mohamad Hanafi Zainal - Kadimin, Ahmad Syakir; Zainal, Mohamad Hanafi (Faculty of Business and Management, 2013)
This study is conducted as a partial fulfillment of the coursework of Industrial Training Project Paper (MKT669). This title of study is “Brand Equity and Customer Repurchase Intention toward Agromas Products”.